Parent-Child Relationships as a Factor in the Development of Self-Regulation in Preschoolers - Seleiman-Holdak, Anastasiia; Kolesnichenko, Lina (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2025)
B a c k g r o u n d. Modern research emphasizes that the development of self-regulation in the preschool age is critically important for the child’s further emotional and cognitive growth. One of the leading factors influencing the formation of the ability to regulate one’s own emotions and behavior is the nature of the parent–child relationship.O b j e c t i v e. The aim of this study was to determine the relationship between the characteristics of parent–child relationships and the level of self-regulation development in older preschool children. The research focuses on identifying which types of mother–child relationships are associated with better or worse abilities of children to exercise emotional control.M e t h o d s. The study was conducted on a sample of 50 mothers of children aged 4 to 6 years. The following methods were used: theoretical (analysis, systematization, and generalization of scientific works and literature on the issue of self-regulation in preschool children); empirical (the Preschool Anxiety Scale by Spence R., Rapee P., McDonald C., and Ingram M.; the Emotion Regulation Checklist by Shields A. and Cicchetti D.; the Parent-Child Relationship Scale by R. C. Pianta; and the Attachment Style Questionnaire by Alexander T., Feeney N., Goaus M., and Noller P.); and statistical-mathematical methods (descriptive statistics, correlation analysis, and regression analysis).R e s u l t s. The findings of the study confirmed the significant relationship between parent–child relationship characteristics and parental attachment style and the levels of anxiety, emotional regulation, and emotional lability in children. Correlation and regression analyses demonstrated that increased emotional lability in children is significantly associated with parent-child conflict and heightened dependence on parents, whereas the development of emotional self-regulation skills is largely supported by an atmosphere of emotional trust and closeness within the family. These results support the hypothesis that parent-child relationships and parental emotional sensitivity are key factors in the development of self-regulation in senior preschool-age children.C o n c l u s i o n s. The results of the study highlight the necessity of supporting parents in developing emotionally balanced relationships with their children to foster the development of children’s self-regulation — an essential factor for successful adaptation to school life and effective learning. Future research should focus on the development and implementation of psychological support programs for families aimed at improving children’s emotional regulation.
Keywords: self-regulation; emotional lability; anxiety; attachment style; child-parent relationship